Peran Pemberian Orientasi Dalam Mengatasi Kecemasan Orang Tua Menghadapi Hospitalisasi Pada Anak Usia Sekolah - I Gusti Ayu Putu Satya Laksmi; I Wayan Erik Febriana; Desak Made Ari Dwi Jayanti (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2021)
The impact of hospitalization on children who are hospitalized can cause an anxiety reaction for parents. Some parental anxiety responses can be minimized by providing a complete orientation to parents regarding the process of hospitalization and treatment of children. This study aims to determine the relationship between orientation and the level of anxiety of parents facing hospitalization in school-age children. This research method uses a descriptive correlation design with a cross sectional approach. The sampling method used is probability sampling with purposive sampling technique. The number of samples in this study were 37 respondents. The data collection tool used is a questionnaire. The data analysis technique used the Spearman Rank (rho) statistical test. The results of data analysis showed the value of r = 0.512 and p-value = 0.001 which means that there is a significant relationship between orientation and the level of anxiety of parents facing hospitalization in school-age children. Giving room orientation to new patients can be said to be good and the level of anxiety experienced by parents is a mild level of anxiety. In connection with the results of this study, the role of nurses is needed in providing a complete orientation to parents whose children are hospitalized so as to reduce the level of parental anxiety.